PANGERAN DRAGWILYA: INSPIRASI KARAKTER PADA FILM BERTEMA DRACULA - Parhepi, Pungky (Institut Seni Budaya Indonesia Bandung, 2018)
Bram Stoker is a novelist with gothic and fictional literary genres in the victorian and edwardian era. The first time he discovered the name of Dracul was when he read a book on Romanian political economy history in the past by William Wilkerson under the title An Account of the Principalities of Wallachia and Moldavia. Dracula is a creation that adapt from time to time. From a novel creation, inspire more other works that are also popular. Conquered film industry in the world, flourishing horror film flows that lifted the main role figure called Dracula or vampire.